Design technologies for green and sustainable computing systems - Ganguly, Amlan; Chakrabarty, Krishnendu; Pande, Partha Pratim (Springer New York, 2013)
This book provides a comprehensive guide to the design of sustainable and green computing systems (GSC). Coverage includes important breakthroughs in various aspects of GSC, including multi-core architectures, interconnection technology, data centers, high-performance computing (HPC), and sensor networks. The authors address the challenges of power efficiency and sustainability in various contexts, including system design, computer architecture, programming languages, compilers and networking. ·         Offers readers a single-source reference for addressing the challenges of power efficiency and sustainability in embedded computing systems; ·         Provides in-depth coverage of the key underlying design technologies for green and sustainable computing; ·         Covers a wide range of topics, from chip-level design to architectures, computing systems, and networks.